Legal Responsibility of Companies in Cases of Personal Data Breaches - Dirgantara, Febrian; Negara, Dharma Setiawan; Darmawan, Didit; Aryanto, Endra Andie; Shahab, Alwi Mohamad (Universitas Pahlawan Tuanku Tambusai, 2025)
Personal data leak cases in Indonesia are becoming an increasingly pressing issue in the digital era. This study aims to analyze the legal responsibility of companies in cases of personal data leaks, identify the main factors causing the incident, and evaluate weaknesses in the existing regulatory and supervisory systems. A normative legal approach is used by reviewing Law Number 27 of 2022 concerning Personal Data Protection and other related regulations. The results of the study indicate that data leaks are caused by weak security infrastructure, low employee awareness, and lack of compliance with data protection standards. Regulatory disharmony and weak supervision are major obstacles in ensuring company compliance with legal obligations. This study recommends improving data security through advanced technology, regulatory harmonization, strengthening supervisory mechanisms, and educating the public about personal data protection rights. Thus, this study is expected to provide practical and theoretical contributions to the development of a more effective personal data protection system in Indonesia.